Territorial governance across Europe. Pathways, practices and prospects. - (:unkn) unknown (Routledge, 2016)
This book provides a comprehensive framework for analysing, comparing and promoting territorial governance in policy relevant research. It reveals in-depth considerations of the emergence, state-of-the art and evolution of the concept of territorial governance. A unique series of ten case studies across Europe, from neighbourhood planning in North Shields in the North East of England to climate change adaptation in the Baltic Sea Region, provides far-reaching insights into a number of key elements of territorial governance. The book draws generalised empirically-based conclusions and discusses modes of transferability of "good practices". A number of suggestions are presented as to how the main findings from this book can inform theories of territorial governance and spatial policy and planning.
Keywords: Raumordnung; Raumentwicklung; Region; Stadtregion; Regionalpolitik; Kooperation; Koordination; Hochwasserschutz; Naturschutzgebiet; Fallstudie; Zusammenarbeit; Grenzüberschreitende Zusammenarbeit; Raumentwicklungspolitik; Nachbarschaftsplanung; Territoriale Governance; Regionale Governance; EU-Projekt; Good Practice